2017
DOI: 10.1007/s40618-017-0619-9
|View full text |Cite
|
Sign up to set email alerts
|

Klinefelter syndrome: cardiovascular abnormalities and metabolic disorders

Abstract: Klinefelter syndrome (KS) is one of the most common genetic causes of male infertility. This condition is associated with much comorbidity and with a lower life expectancy. The aim of this review is to explore more in depth cardiovascular and metabolic disorders associated to KS. KS patients have an increased risk of cerebrovascular disease (standardized mortality ratio, SMR, 2.2; 95% confidence interval, CI, 1.6-3.0), but it is not clear whether the cause of the death is of thrombotic or hemorrhagic nature. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 55 publications
0
42
0
2
Order By: Relevance
“…Data from recent large registry-based studies reported a significant increase in mortality risk by 40% (hazard ratio (HR) for all-cause mortality = 1.40; HR cardiovascular mortality = 1.41) [14] with a standardized mortality ratio (SMR) of 1.5 [15], corresponding to a significantly reduced median survival of 2.1 years. Patients with KS are more frequently insulin resistant, obese and prone to develop type 2 diabetes mellitus (T2D) [18,19], a condition considered a CVD equivalent. The onset of T2D in patients with KS is a turning point in worsening of the CVD risk profile.…”
Section: Introductionmentioning
confidence: 99%
“…Data from recent large registry-based studies reported a significant increase in mortality risk by 40% (hazard ratio (HR) for all-cause mortality = 1.40; HR cardiovascular mortality = 1.41) [14] with a standardized mortality ratio (SMR) of 1.5 [15], corresponding to a significantly reduced median survival of 2.1 years. Patients with KS are more frequently insulin resistant, obese and prone to develop type 2 diabetes mellitus (T2D) [18,19], a condition considered a CVD equivalent. The onset of T2D in patients with KS is a turning point in worsening of the CVD risk profile.…”
Section: Introductionmentioning
confidence: 99%
“… 32 In patients with low T levels, several studies have highlighted a higher prevalence of cardiovascular events. 33 , 34 In 2011, two meta-analyses were performed: the first included 70 studies with over 12,500 patients and showed that patients with CVD have significantly lower T and higher E2 levels than patients without CVD. This finding was confirmed by a logistic regression, after adjustment for age and BMI.…”
Section: Effects Of Testosterone Replacement Therapy On the Cardiovasmentioning
confidence: 99%
“…Mindemellett fontos, hogy a nagyobb cardio-és cerebrovascularis, trombotikus, illetve metabolikus megbetegedési rizikó [31] mérséklése érdekében tartsuk szem előtt a minél korábbi prevenciót. Az X-kromoszóma-többlettel járó kórképben a centrális típusú elhízás és az ahhoz gyakran társuló anyagcserezavarok -mint a hyperlipidaemia, az inzulinrezisztencia, a csökkent glükóztolerancia, a kettes típusú cukorbetegség -kombinált terápiával megelőzhetők és gyógyíthatók.…”
Section: Klinefelter-szindrómaunclassified